A grande seca de 1979 a 1983: um estudo de caso das ações do governo federal em duas sub-regiões do estado do Ceará (Sertão Central e Sertão de Inhamuns) - Campos, Nivalda Aparecida (Universidade Federal de São Carlos, 2004)
The subject of this article is the State intervention in two macro regions of the Brazilian state of Ceará: Central Hinterlands and Inhamuns Hinterlands during the hard drought of 1979-1983. The objective was to identify why the effects of the weather phenomenon were so catastrophic even with the governmental programs being developed. During the researches, it was observed that the principles and strategies that orientate the intervention in the semi-arid Northeast region has been conservative and concentrative, beneficiating only certain groups.
Keywords: Sociologia política; Brasil, Nordeste; Secas; Ceará; Políticas públicas; Estado; CIENCIAS SOCIAIS APLICADAS